U.S. POINTER (USA): World‐Wide FINGERS network: The first global network of multidomain dementia prevention trials. (7th December 2020) - Baker, Laura D.; Espeland, Mark A.; Kivipelto, Miia; Whitmer, Rachel A.; Snyder, Heather M.; Carrillo, Maria C.; Antkowiak, Susan; Chavin, Melanie; Cleveland, Maryjo; Day, Claire E.; Desai, Pankaja; Elbein, Richard; et al.
Abstract: Background: U.S. POINTER aims to test whether a multidomain lifestyle intervention focused on physical and cognitive activity, nutrition, and risk factor management reduces risk of cognitive decline in a heterogeneous population of older adults in the U.S. The study adapts the FINGER (Finnish Intervention Geriatric Study to Prevent Cognitive Impairment and Disability) interventions to fit American culture and works with community partners at 5 sites across the country to develop sustainable community‐based intervention programs. Methods: U.S. POINTER is a 2‐year RCT that is enrolling 2000 cognitively normal older adults (60‐79 years) who are at risk for decline due sedentary lifestyle, poor diet and other factors such as family history of memory impairment and suboptimum cardiovascular health. Recruitment utilizes electronic health records, as well as grassroots approaches to engage traditionally underrepresented groups. Participants are randomized to one of two lifestyle intervention groups – Self‐Guided or Structured Lifestyle Intervention – that differ in format, intensity and accountability. U.S. POINTER includes partnerships with local chapters of the Alzheimer's Association and lifestyle specialists to assist with intervention delivery. The primary outcome is 2‐year change in cognitive function measured with a composite score that permits harmonization with FINGER. Results: Recruitment began in 2019 at the vanguard site in North Carolina. Study progress at all 5 participating sites will be presented. Progress toward harmonization with FINGER and other international study teams in the WW‐FINGERS network will also be discussed. Conclusion: As a member of the WW‐FINGERS network of trials, U.S. POINTER provides an unprecedented opportunity to leverage lessons learned in FINGER and expand this work to test the generalizability of the findings to a heterogeneous American cohort with different cultural needs and practices. The results, in combination with those from other WW‐FINGERS studies, have the potential to identify a strategy to slow cognitive decline on a global scale.